Evaluation of a calf starter supplement - J.L. Morrill; P.G. Reddy (Kansas Agricultural Experiment Station Research Reports, 1987)
An experimental calf starter made from a pelleted commercial type supplement and feeds readily available on the farm was compared to a conventional pelleted calf starter in an attempt to demonstrate an economical alternative to commercial calf starter. Calves fed the experimental starter consumed as much starter and gained as much weight as calves fed the conventional starter, thus demonstrating a potential for savings on feed cost. The project is continuing in an attempt to improve the starter composition.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Calf starter supplement; Feed cost; Weight gain; Consumption